Air quality during COVID-19 pandemic forced partial confinement in Turkey - Genceli, Hadi (INDERSCIENCE ENTERPRISES LTD, 2022)
The increasing trend of COVID-19 cases led the Turkey Government to announce some restrictions in 3 April 2020. The purpose of this research is to assess the influence of the COVID-19 forced partial confinement on air pollution of three most polluted and crowded cities of Turkey. After some days of imposing restrictions, atmospheric pollutant concentrations in terms of different pollution parameters remarkably dropped. The data reveals that, the most considerable improvement was observed for Ankara and NO2 (-50.9%) which is attributed to the limitation of vehicular movement. In addition, the lowest reduction in air pollution parameters was recognised for Istanbul and SO2 (-1.7%). During the period of partial confinement in Turkey (3rd April to 3rd May), O-3 concentration increased by about 30.9%, 31.8% and 17.4% in Istanbul, Ankara and Bursa in contradiction to remaining pollutants which is the consequence of lower titration of ozone by NOx resulting in accumulation of O-3.
Keywords: carbon monoxide; COVID-19; nitrogen dioxide; ozone; partial confinement; particulate matter; sulphur dioxide; Turkey; GLOBAL BURDEN; POLLUTION; DISEASE; SO2; Environmental Sciences & Ecology